2013
DOI: 10.7150/ijbs.6739
|View full text |Cite
|
Sign up to set email alerts
|

Hoxc Gene Collinear Expression and Epigenetic Modifications Established during Embryogenesis Are Maintained until after Birth

Abstract: The Hox genes, which are organized into clusters on different chromosomes, are key regulators of embryonic anterior-posterior (A-P) body pattern formation and are expressed at specific times and in specific positions in developing vertebrate embryos. Previously, we have shown that histone methylation patterns are closely correlated with collinear Hox gene expression patterns along the A-P axis of E14.5 mouse embryos. Since histone modification is thought to play a crucial mechanistic role in the highly coordin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
2
2
0
Order By: Relevance
“…As summarized in figure 6 , we found that genomic sequences flanking Hoxb4–6 genes, including RAREs controlling their expression in the neural tube, were clearly enriched for H3K27me3 marks in rostral NSPC cultures in comparison with caudal NSPCs, whereas H3K4me3 and H3K9/14ac marks showed opposite profiles. While lacking the power of high-throughput approaches, our results usefully complement previous data obtained with dissected explants from head and trunk regions of developing mice [ 57 , 59 , 61 , 62 ]. By taking advantage of culture conditions allowing symmetric NSPC self-renewal in vitro [ 40 ], our work provides comparison of nearly homogeneous populations of NSPCs, rather than tissue fragments where neural progenitors coexist with differentiated cells and non-neural cell types.…”
Section: Discussionsupporting
confidence: 79%
“…As summarized in figure 6 , we found that genomic sequences flanking Hoxb4–6 genes, including RAREs controlling their expression in the neural tube, were clearly enriched for H3K27me3 marks in rostral NSPC cultures in comparison with caudal NSPCs, whereas H3K4me3 and H3K9/14ac marks showed opposite profiles. While lacking the power of high-throughput approaches, our results usefully complement previous data obtained with dissected explants from head and trunk regions of developing mice [ 57 , 59 , 61 , 62 ]. By taking advantage of culture conditions allowing symmetric NSPC self-renewal in vitro [ 40 ], our work provides comparison of nearly homogeneous populations of NSPCs, rather than tissue fragments where neural progenitors coexist with differentiated cells and non-neural cell types.…”
Section: Discussionsupporting
confidence: 79%
“…E14.5 embryos were dissected into three parts, brain, trunk anterior, and trunk posterior tissues, and then semi-quantitative RT-PCR was performed after isolating total RNA from each tissue. In agreement with previous reports ( Kwon et al, 2005 ; Min et al, 2012 ; 2013 ), Hoxc8 was strongly expressed in the trunk anterior and moderately expressed in the trunk posterior; it was not expressed in the brain ( Fig. 3 ).…”
Section: Resultssupporting
confidence: 93%
“…Spatiotemporal collinear expression of Hox gene along the A–P axis in mouse embryos appears to be a consequence of epigenetic modifications of chromatin in which the 3' active domain (euchromatin) proceeds to posterior 5′ genes in the Hox cluster during development . Since separation of active and inactive domains in chromosomes is reported to be demarcated by the insulator binding protein CTCF in the chromatin barrier region , we next analyzed CTCF binding in the Hoxc cluster in both WT and Akt1 null MEFs.…”
Section: Resultsmentioning
confidence: 99%